Congratulations, recipients of digital content creation 2022 - Noraisah Nurul Fatwa, Mohd Razali; Nor Yazi, Khamis (Pusat Bahasa Moden UMP, 2023)
As educators progressively shift from print to digital instructional materials, the educators’ exertion to creatively digitalised the materials merit some recognition.